The use of social media among the academic elite in the Kurdistan Region and its role in developing their political awareness - Rawan Subhi Obaidullah; Rebar Goran Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study attempts to find out the extent of using social media among the academic elite in the Kurdistan Region and its role in developing their political awareness. This study is of the type of descriptive studies, and the survey method was used for a cluster random sample of (391) individuals from the universities of (Dohuk-Erbil-Sulaymaniyah-Halabja). This study reached several results, the most important of which are: The extent of social media use among the research sample is the Facebook network in the first place. Refers to the channels of diplomatic communication between the governments of the region and Baghdad on social media in a clear way about handling the file of disputes between the governments of the region and Baghdad.